The Effect of Education on Geographic Mobility: Incidence, Timing, and Type of Migration - Abdurrahman Aydemir; Murat G. Kirdar; Huzeyfe Torun (Institute of Labor Economics (IZA), 2021)
We take advantage of a major compulsory school reform in Turkey to provide novel evidence on the causal effect of education on both the incidence and timing of internal migration. In addition, for the first time in literature, we provide causal effects of education on migration by reason for migration. We find that while education substantially increases the incidence of migration among men, there is no evidence of an effect among women. Women, however, become more likely to migrate at earlier ages and their migration reasons change. Revealing the empowering role of education, women become more likely to move for human capital investments and for employment purposes and less likely to be tied-movers.
Keywords: J61; I2; 330; education; internal migration; incidence and timing of migration; reason for migration; 2SLS; regression discontinuity design